Competitive priorities for the LNGPac™ in the merchant market segment - Rönngren, Christopher (My University, 2021)
The everchanging business environment in combination with the requirements from different markets offer both opportunities as well as threats for organizations. Capitalization on those opportunities, by investing in correct capabilities and resources, will generate future business success. However, determining the right objectives and priorities for investment to acquire competitive advantage is a major challenge for organizations. Sustaining the competitive advantage requires sensing of the market’s requirements and appropriate response from the organization. By understanding the market requirements, an organization can identify which competitive priorities are of essence in a certain market. In order to address the competitive priorities correctly, the organization’s operations strategy and resource allocation should be aligned with the identified competitive priorities. Thus, the aim of this research is to identify the competitive priorities in the merchant market segment with regards to the LNGPac™ and how well the case company’s, Wärtsilä’s, existing operations strategy and resource-allocation are supporting the identified competitive priorities. The research utilizes the sense and respond methodology in combination with manufacturing strategy index method to identify the competitive priorities and understand the alignment between them and the current operations strategy and resource allocation. In addition, this research measures the sustainable competitive advantage of Wärtsilä’s current operations strategy with regards to the merchant market segment and the LNGPac™. The data for this study is collected internally within Wärtsilä through e-mail questionnaires and a web-questionnaire. The result of the study is validated through a semi-strong market test performed in collaboration with experts within Wärtsilä. The research followed the steps from the framework Justification of Strategy Uninterrupted (JOSU). This study identified the key competitive priorities in the merchant market segment that requires attention to increase the competitiveness of the LNGPac™. Additionally, the research identified some misalignment between current operations strategy and the competitive priorities. However, the existing operations strategy is deemed sustainable. Thus, the core challenge is to keep it sustainable while aligning it with the identified competitive priorities in the merchant segment.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management